Isolation and characterization of pigmented bacteria for dye sensitized solar cell application - Yek, Lily Siew Ling (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Natural bacterial pigment from the microorganism was an attractive alternative choice of photosensitizers in dye-sensitized solar cells. In this study, Paracoccus sp that are able to produce astaxanthin and bacterium capable of melanin production on nutrient agar were isolated and identified through biochemical test and DNA gene sequencing method. Bacterial pigments were purified and characterized using Thin Layer Chromatography, Gas Chromatography- Mass Spectrophotometer, Ultraviolet-visible, and Fourier Transform Infrared Spectroscopy analysis. Dye-sensitized solar cell that apply brown bacterial pigment as organic dye produce 63.4 mV at the 3`l day while dye-sensitized solar cell that apply orange bacterial pigment as organic dye produce 49.6 mV at the 3'd day.